Geometric indexes of heart rate variability in healthy individuals exposed to long-term air pollution - Regis da Costa e Oliveira, Juliana; Base, Luis Henrique; Maia, Laura Cristina Pereira; Ferreira de Lima Antão, Jennifer Yohanna Ferreira; de Abreu, Luiz Carlos; Oliveira, Fernando Rocha; Vanderlei, Luiz Carlos Marques [UNESP]; Filho, Celso Ferreira; Ferreira, Celso (Springer Nature, 2020)
The aim of this study was to investigate the autonomic modulation of heart rate in healthy individuals exposed to long-term air pollution through geometric methods. We analyzed data from 109 healthy adults aged 18 to 49, divided into three groups according to the exposure time: period 0 to 15 years of exposure (n = 29), more than 15 years of exposure (n = 31), and control group (n = 49). For the analysis of heart rate variability (HRV), heart rate was recorded beat-to-beat for 20 min in the sitting position. The RR intervals were transformed into geometric indexes, and from them, we calculated the RRTri (triangular index), TINN (triangle interpolation of histogram of intervals NN), and Poincaré plot (SD1, SD2, and SD1/SD2). Significantly lower values were observed in the group of individuals exposed to air pollution for more than 15 years compared with the group of individuals exposed to air pollution for a period of 0–15 years and those not exposed for the RRTri (11.5 vs 13.8 vs 14.0), SD1 (16.4 vs 20.5 vs 20.6), SD2 (60.5 vs 68.1 vs 72.5), and SD1/SD2 (0.27 vs 0.34 vs 0.31), with the effect of this difference being considered large (RRTri), medium (SD1, SD1/SD2), and small (SD2). TINN was not significantly different among groups (198.2 vs 223.1 vs 233.6). Healthy individuals exposed to air pollution for more than 15 years present an autonomic imbalance, characterized by lower parasympathetic modulation and overall HRV.
Keywords: Air pollution; Autonomic nervous system; Cardiovascular system; Environmental pollution